The social self and social death: Rethinking reparations for genocide and crimes against humanity - Marsoobian, A.T. (Pragmatism Today, 2020)
Based on a pragmatist inspired conception of the social self, the concept of reparations for the harms of genocide is reexamined. Both Raphael Lemkin, the person who invented the term “genocide,” and Claudia Card, a philosopher who examined the evil of genocide, hold similarly expansive notions of the harms inflicted by genocidal violence. Both argued that biological death is not necessarily central to genocide. For Lemkin cultural destruction of the targeted group is just as essential as the actual killing itself. Genocide is a group crime that aims to destroy the group and all the social aspects of group identity. Card similarly sees the target of genocidal violence as the social vitality of the self. This vitality is sustained by group relations. Reparations thus need to be reconceptualize in terms of the restoration of social life of the victim group and not solely on the basis of economic losses. Examples are given for the reparation of the social vitality of communities that have suffered genocide. © 2020 Central European Pragmatist Forum. All rights reserved.
Keywords: Claudia Card; Genocide; Raphael Lemkin; Reparations; Social death; Social self; dept.phi; peer-reviewed; ⛔ No DOI found

The Armenian Genocide of 1915: Armen T. Marsoobian explores the complex history of one of the 20th-century's worst and most neglected crimes against humanity - Marsoobian, A.T. (History Today, 2015)
Keywords: dept.phi; ⛔ No DOI found

Saying, singing, or semiotics: "Prima la musica e poi le Parole" revisited - Marsoobian, A.T. (Journal of Aesthetics and Art Criticism, 1996)
2 citations (Crossref) [2023-10-31]
Keywords: dept.phi

Why Controlling the Historical Narrative Matters: A Jamesian Response - Marsoobian, A.T. (Pragmatism Today, 2022)
An examination of the lessons learned from William James’s oration on the dedication of the Civil War Monument memorialization Colonel Robert Shaw and the Fifty-Fourth Regiment Massachusetts Infantry, an all-Black unit. The role of monuments in making visible the values of a society is explored in the context of promoting a nation’s historical narrative, in particular in their propagation of the South’s Lost Cause narrative. The genocidal violence against Armenians in the Caucasus by the Azerbaijani regime serves as the second illustration of the abuse of historical narratives. © 2022 Central European Pragmatist Forum. All rights reserved.
Keywords: Armenians; Azerbaijan; Civil War monuments; William James; civic courage; dept.phi; genocidal violence; historical narratives; peer-reviewed; the Lost Cause; ⛔ No DOI found

Aesthetics - Marsoobian, A.T. (The Bloomsbury Handbook of Pragmatism, 2024)
Keywords: dept.phi

Editors' Introduction - Lindert, J.; Marsoobian, A.T. (Multidiscipl. Perspect. on Genocide and Memory, 2018)
Journal Abbreviation: Multidiscipl. Perspect. on Genocide and Memory
Keywords: dept.phi